The literary impulse of François-René Auguste de Chateaubriand - Carminatti, Natália Pedroni (Lettres Françaises, 2019)
Reflecting on the eighteenth-century French Literature requires revisiting the poetics of François-René Auguste de Chateaubriand. The importance of this writer to the Literary Studies marked a series of influences in the movement titled Romanticism. Having said this, the present article aims to present the emergence of Chateaubriand’s artistic consciousness as well as to emphasize the importance of his particular universe in his literary works. In order to do so, a biographical journey is made, naming those who helped him in this endeavor. In this sense, we turn to Mémoires d’outre tombe (1849-1850) in which the explanations provided by the author based his literary thinking. America also played a key role in his personal maturation process.